Istihsan in Determination of the Lunar Month: Jurisprudential Flexibility for Harmonizing the Ummah - Ananda Sy, Geubrina Rizky; Qiromi, Nur Mahmudi; Mahsun, Mahsun; Tajrid, Amir (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This article examines the role of Istihsan as a method of Islamic jurisprudential flexibility in determining Islamic law, particularly regarding the beginning of the lunar month, and reviews the positions of the four prominent schools of jurisprudence (Hanafi, Maliki, Hanbali, and Shafi'i) toward its application. Istihsan, which etymologically means